2016
DOI: 10.1039/c5nr07773g
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin loaded dual pH- and thermo-responsive magnetic nanocarrier for combined magnetic hyperthermia and targeted controlled drug delivery applications

Abstract: Magnetic nanocarriers have attracted increasing attention for multimodal cancer therapy due to the possibility to deliver heat and drugs locally. The present study reports the development of magnetic nanocomposites (MNCs) made of an iron oxide core and a pH- and thermo-responsive polymer shell, that can be used as both hyperthermic agent and drug carrier. The conjugation of anticancer drug doxorubicin (DOX) to the pH- and thermo-responsive MNCs via acid-cleavable imine linker provides advanced features for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
127
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(137 citation statements)
references
References 53 publications
5
127
1
Order By: Relevance
“…Hydrogen bonds and van der Waals interactions can also be considered but the main interactions that allow the drug penetration within the polymer shell are the apolar interactions. 32,33 Supramolecular interactions were used to encapsulate the drug for two main reasons, rst to evaluate the stability of the encapsulation by those weak associations, second to develop a system that can release quickly with temperature without the need of a further step of drug linkage as it is the case when the drug is covalently graed at the NPs surface. Indeed, while the copolymer chains are swollen below the LCST thanks to the hydrogen bonding with water, DOX can diffuse within the copolymer shell and be blocked by the apolar interactions with the polymer backbone.…”
Section: Resultsmentioning
confidence: 99%
“…Hydrogen bonds and van der Waals interactions can also be considered but the main interactions that allow the drug penetration within the polymer shell are the apolar interactions. 32,33 Supramolecular interactions were used to encapsulate the drug for two main reasons, rst to evaluate the stability of the encapsulation by those weak associations, second to develop a system that can release quickly with temperature without the need of a further step of drug linkage as it is the case when the drug is covalently graed at the NPs surface. Indeed, while the copolymer chains are swollen below the LCST thanks to the hydrogen bonding with water, DOX can diffuse within the copolymer shell and be blocked by the apolar interactions with the polymer backbone.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Feraheme (ferumoxytol, AMAG Pharmaceuticals), which is clinically approved for iron replacement therapy in chronic kidney disease, has been investigated as marker for the presence of macrophages in solid tumours253, and has recently been shown to modulate the activity of these macrophages towards a proinflammatory, anti-tumoural phenotype75. There are several additional promising applications of SPIONs, such as using their magnetic properties and localisation tumours to create local hyperthermia by applying an alternating magnetic field (NanoTherm, MagForce AG), or using them as drug carriers that release their payload as a result of magnetically induced heating254. While SPIONs are generally considered non-toxic, it is important to realise that there is no physiological route of iron excretion from the human body, other than a passive intestinal loss that is typically limited to 2 mg iron per day.…”
Section: Iron Oxide Nanoparticlesmentioning
confidence: 99%
“…It is reported that the nanoparticles with a size of 10-200 nm can passively accumulate in the tumor cells via the enhanced penetration and retention effect. 28 The graed PEG chain could also increase the hydrophilicity of the micelles and serve as a shielding polymer to avoid the potential recognition by the reticuloendothelial system that is primarily responsible for the capture of ectogenic nanoparticles. Moreover, FA as a widely adopted targeting moiety was capable of specically targeting the FA receptor that overexpressed in various types of cancer.…”
Section: Morphology and Size Distributionsmentioning
confidence: 99%